The Impact of Foot Care Education on Knowledge of Prevention the Risk for Diabetic Ulcers Among Diabetic Patients - Isni Hijriana; Irma Yunita; Syatria Wati; Meutia Chaizuran; Ayi Nadasiah (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Diabetic foot ulcers are the fastest growing chronic complications of diabetes mellitus, unmanaged diabetic complications such as diabetic foot ulcers will have a negative impact on the quality of life of individuals, health education, information and communication about DFUand foot care needs to be improved. The purpose of this study was to determine the impact of foot care education on knowledge of diabetic ulcer risk prevention in people with diabetes mellitus in the working area of the Mutiara Barat Health Center, Pidie Regency. This type of research is quasi-experimental research. The population in this study were all diabetes mellitus sufferers in the working area of the Mutiara Barat Health Center, Pidie Regency, in the last 1 month as many as 63 patients. Sampling was done purposive sampling technique as many as 25 people. The results showed that there was an effect of foot care education on knowledge of diabetic ulcer risk prevention in people with diabetes mellitus in the working area of the Mutiara Barat Health Center, Pidie Regency, which obtained a significance value of ρ = 0.001 where ρ <0.05. Health education provides moderate to moderate knowledge in helping diabetes mellitus patients to increase their knowledge about diabetic foot ulcer prevention. It is hoped that good knowledge will raise awareness, will and strength, so that it can change the behavior of diabetes mellitus patients into adaptive behavior that can prevent diabetic ulcers from occurring.